Koncepcja pedagogiczna i program leśnych przedszkoli na przykładzie przedszkola w Lipsku na terenie Niemiec - Agnieszka Janik (Problemy Wczesnej Edukacji)
This article is the result of the author’s study visit that took place in the forest kindergarten “Wurzeln & Flügel e.V.” in Leipzig, Germany on 23–27th of July 2014. The study visit created an opportunity for the author to participate in the educational process in its unique environment – in the park. This publication is an attempt to describe the observed reality of a forest kindergarten, especially in terms of its pedagogical dimension.